Troy D. Zars: a personal tribute to a scientist, colleague, and friend. (2nd January 2020) - Schulz, David J.
Abstract: I knew Troy for nearly 15 years, and in that time I don't recall hearing any childhood stories like those in seemingly every personal statement I've read from aspiring scientists or medical students. No stories about hours spent gazing at an anthill. I don't recall hearing about shelves crowded with insects collected on Styrofoam, or animal skulls kept in a shoebox under his bed. If these collected crania existed, it was more likely because Troy was a crack shot with a pellet gun than a need to know adaptations in the dentition of local squirrel populations. I don't recall hearing about science projects taken to the Iowa State Capitol to share with politely interested legislators. But I do recall hearing about spending the entirety of the daylight hours in the summer, with his brother Doug, finding where the crappie were biting. About crystal clear water on a lake in Minnesota that you didn't quite need to know the exact location of, just in case you were thinking of going and plundering the walleye within. I definitely heard about triumphs as a starting lineman not only for his high school football team, but the mighty Norse of Luther College. I heard about summer warehouse jobs in sweltering Iowa Julys. And I saw, firsthand, love and commitment and family. Troy's story demonstrates that the finest scientists are not just cultivated in narrow STEM curricula that begin at age 5. They are just as likely to be football-playing fishermen, fathers, husbands, and friends who can navigate an operant conditioning paradigm during the week, and dance a polka and produce a magnificent smoked pork shoulder on Saturday. Nature and an independent spirit and a little bit of mischief is a different kind of Magnet school. And it gave us truly one of the best.